Josefa Verride y Martina de los Ángeles. El difícil camino hacia la santidad. - ACÍN, ANA MORTE (Scripta, 2016)
Through the information provided to us the lives of Josefa Verride lay sister of dominican order in Huesca and Martina of the Angels, nun of the same order, founder of the convent of s. Pedro in Benabarre, I intend to bring new ideas about the process of acquiring reputation of holiness of some women in the Early Modern age in Spain. Religious orders had to devise strategies that helped legitimize and consolidate the reputation of holiness of these women. One of these strategies was to link them with other women religious with a reputation for holiness, creating female genealogies to enable them perpetuate their memory and prestige over time.